Omega 3 and Omega 6 fatty acids sources and health benefits – A Review - P, Deeksheetha; M, Anitha; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Omega-3 fatty acids are poly unsaturated fatty acids. The fish-derived omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are helpful in development, cardiovascular function, and Alzheimer’s disease. However, because our bodies do not efficiently produce some omega-3 fatty acids from marine sources, it is necessary to obtain adequate amounts through fish and fish-oil products. EPA and DHA, when deficient may affect many aspects of cardiovascular function including inflammation, peripheral artery disease, major coronary artery disease.